Design and fabricate of portable cnc milling machine - Siti Aina Mardhia, Dol Haji (2013)
In manufacturing industry, portable CNC milling machine is important to produce a product. This project describes a design and fabrication of portable CNC milling machine. This project utilized operating principles of CNC milling machine where it can move in 3 axes specifically X, Y and Z. For this project Master CAM software was used to generate the G-code for milling cutting construction testing. The most important part is the holder of the spindle, without a strong spindle holder it because difficult to produce good quality products. This project develop a CNC machine in combination with a computer. Parallel port was utilized together with intermediate Mach3 software to move the machine during cutting process. The purpose of this project is to develop a low-cost project portable CNC milling machine. It can be transported using minimum manpower, easily handled and also suitable for small industry. AC power supply is used and sent to the noise filter to reduce signal interference before sent to the stepper motor to allow axes X, Y and Z move. CNC machine structure movement is controlled by the DC stepper motor. For example, when DC stepper motor gets signal, it was sent to the gear box and turn the ball screw that connect with each drivers X, Y and Z through the bearing. Then, the driver X, Y and Z moving to start cutting process according to the computer instruction until the cutting done.